Overexpression of IL-8 augments the susceptibility to a hyperinflammatory phenotype in pediatric acute respiratory distress syndrome and correlates with adverse outcomes: a retrospective two-center study conducted in northwest China - Wang, Yi; Wang, Weikai; Lv, Zhe; Wu, Haitong; Zhang, Hua; Wang, Ying; Zhou, Yong; Guo, Zhangyan; Li, Jingmei; Ma, Le; Yao, Dan; Zhang, Taining; et al. (Frontiers in Pediatrics, 2026)
BackgroundThe prognosis of acute respiratory distress syndrome (ARDS) varies with inflammatory responses. ARDS patients with a hyperinflammatory phenotype usually have worse alveolar epithelial injury and vascular endothelial injury than those carrying a hypoinflammatory phenotype. Activated neutrophils recruited and migrated in the lung tissue are responsible for stimulating the progression of ARDS. Interleukin-8 (IL-8), as an inflammatory factor, further aggravates lung damage in ARDS.MethodsThis was a retrospective study involving 135 ARDS children admitted in two pediatric hospitals in northwest China. They were either classified into mild, moderate and severe groups based on the oxygenation index (OI) or oxygenation saturation index (OSI) within 4-h invasive mechanical ventilation on admission, or the survival and non-survival groups based on the 28-day mortality. Demographic and clinical data were analyzed. Risk factors for the prognosis of PARDS were identified by logistic regression. The correlation of IL-8 level with the identified risk factors was analyzed. Prognostic potential of IL-8 was determined by plotting the receiver operating characteristic (ROC) curves.ResultsIL-8, RAGE, Ang-2, ICAM-1 and SP-D were independent risk factors for the mortality of PARDS. They were significantly higher in the non-survival group than the survival group, showing a potential in predicting mortality in PARDS, especially in the combination (P < 0.05). IL-8 was positively correlated with RAGE, Ang-2, ICAM-1 and SP-D in children with ARDS (P < 0.05).ConclusionIL-8 is overexpressed in children with ARDS, showing a prognostic potential particularly in combination with RAGE, Ang-2, ICAM-1 and SP-D in PARDS.